POLICY IMPLEMENTATION APPOINTMENT OF PRINCIPAL FROM MOVER TEACHERS IN WEST NUSA TENGGARA PROVINCE IN 2024 (IMPLEMENTATION OF MINISTER OF EDUCATION, CULTURE, RESEARCH AND TECHNOLOGY REGULATION NUMBER 40 OF 2021) - I Ketut Budiarthi; Agus Joko Purwanto; Muhammad Nur Affandi (RADJA PUBLIKA, 2024)
The implementation of the principal appointment policy in West Nusa Tenggara Province in 2024 has not met government expectations. This policy is based on the Ministry of Education, Culture, Research, and Technology Regulation Number 40 of 2021 concerning the assignment of teachers as principals. The requirement for mover teacher to become principals, as stipulated in Article 2, paragraph c, has not been fully implemented, even though two years have passed since the regulation was enacted and the availability of teacher leader competency certificates has been met. This study aims to analyze the implementation of the policy of appointing principals from teacher leaders from the aspects of communication, resources, disposition, and bureaucratic structure. The next objective is to reveal the inhibiting and enabling factors in the implementation of the policy. This is a qualitative study using a post-positivist approach, where data processing and analysis use the DAPA (Data Analysis Procedure by Application) technique with Nvivo 12 Plus. This study found that the implementation of principal appointments in three regional governments, namely West Lombok Regency, West Sumbawa Regency, and the Provincial Government, has been carried out in stages, both manually and through the implementation of the KSPS system. In terms of communication, the policy implementation was conveyed to regional governments through the provincial education office and district/city education offices through socialization activities, workshops, and coordination meetings. Supporting resources for this policy have been almost fully provided by the government. The disposition or attitude of the implementers generally supports this policy. The bureaucratic structure of the policy has been designed by the government, so regional governments feel that there is no need to develop SOPs, supported by the use of the KSPS system, which has various advantages such as automated administrative selection, integration with the dapodik, ekinerja, PMM, and other systems that simplify the appointment communication process. The revelation of inhibiting and supporting factors, as well as the analysis of the implementation of this policy, has resulted in a new, more comprehensive, and participatory policy implementation model/strategy.